Insect Fauna Visiting Cassava Plot in Thong Saen Khan District, Uttaradit Province - คงเจริญ พัทธเมธา; โพธิ์นาค เกียรติศักดิ์; สิทธิกุล สราวุติ; พรหมน้อย สิริวดี; พูลประเสริฐ พิสิษฐ์ (YRU Journal of Science and Technology, 2018)
Insect fauna occurring in cassava plot from Thong Saen Khan district, Uttaradit province were surveyed during February to June 2017 by using malaise trap, sweep net and hand collecting. It was exposed that 66 insect species, 41 families under nine orders were recorded. In this regard, species diversity (H’) and Simpson index (D) for all insect of all techniques were 3.14 and 0.91 respectively whereas using sweep net held the highest value of Evenness (J’) (0.92). Nonetheless, the highest insect species diversity index (H’), Evenness (J’) and Simpson index (D) from malaise trap gained from the pooled data set of this observation were 2.93, 0.84 and 0.91. While all ecological diversity indices obtained from hand collecting showed the lowest values of 1.14, 0.32 and 0.54, respectively. For similarity index (Ss), the insect community recorded among different methods shared ranging from 0.03 - 0.40. Besides, Edwardsiana bergmanni (F. Cicadellidae) considering as insect pest was the dominant species (10.56%). Whilst, Micraspis crocea (F. Coccinellidae), a natural enemy, was mainly found in this survey (13.79%). In addition, when the survey stopped it was revealed that the accumulation curve in all study sites of cassava insect was still rising gradually. It might be possible that the insect species would be increased if we continue to survey more in next stage. The basic data from this present observation was able to be adopted as guideline in integrated pest management of cassava cultivation.